THE METHODOLOGY OF DEVELOPING STUDENTS’ DESIGN THINKING THROUGH THE USE OF AUTOMATED DESIGN SYSTEMS - Xazratqulov Abduvohid (International Scientific and Current Research Conferences, 2025)
The growing ubiquity of automated design systems (ADS) in engineering and creative industries demands new pedagogical approaches that embed such tools into learning environments while cultivating students’ design-thinking competences. This study proposes and tests an instructional methodology that situates ADS at the centre of a problem-based design studio. A quasi-experimental implementation with second-year mechanical-engineering students compared an ADS-rich studio to a conventional CAD laboratory over one semester. Mixed-methods evaluation revealed significant gains in empathic problem scoping, ideation fluency and iterative prototyping in the experimental cohort, without compromising technical accuracy. The findings indicate that ADS, when framed by a human-centred design-thinking cycle and supported by reflective dialogue, can accelerate skill acquisition and deepen conceptual understanding of the design process. Recommendations for curriculum designers focus on sequencing, feedback orchestration and assessment alignment to sustain the positive effects.